Identifying Worldviews on Corporate Sustainability: A Content Analysis of Corporate Sustainability Reports - Landrum, Nancy E.; Ohsowski, Brian (Business strategy and the environment, 2018)
Companies commonly issue sustainability or corporate social responsibility (CSR) reports. This study seeks to understand worldviews of corporate sustainability, or the corporate message conveyed regarding what sustainability or CSR is and how to enact it. Content analysis of corporate sustainability reports is used to position each company report within stages of corporate sustainability. Results reveal that there are multiple coexisting worldviews of corporate sustainability, but the most dominant worldview is focused on the business case for sustainability, a position anchored in the weak sustainability paradigm. We contend that the business case and weak sustainability advanced in corporate sustainability reports and by the Global Reporting Initiative are poor representations of sustainability. Ecological embeddedness, or a locally responsive strategy that is sensitive to local ecosystems, may hold the key to improved ecological sensemaking, which in turn could lead to more mature levels of corporate sustainability worldviews that support strong sustainability and are rooted in environmental science. This must be supported by government regulation. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment